Detection and Characterization of Bat Sarbecovirus Phylogenetically Related to SARS-CoV-2, Japan - Murakami, Shin; Kitamura, Tomoya; Suzuki, Jin; Sato, Ryouta; Aoi, Toshiki; Fujii, Marina; Matsugo, Hiromichi; Kamiki, Haruhiko; Ishida, Hiroho; Takenaka-Uema, Akiko; Shimojima, Masayuki; Horimoto, Taisuke (Emerging infectious diseases, 2020)
Epidemiology of bat Betacoronavirus, subgenus Sarbecovirus is largely unknown, especially outside China. We detected a sarbecovirus phylogenetically related to severe acute respiratory syndrome coronavirus 2 from Rhinolophus cornutus bats in Japan. The sarbecovirus' spike protein specifically recognizes angiotensin-converting enzyme 2 of R. cornutus, but not humans, as an entry receptor.